The Influence of Modern Sports on Local Community Recreational Sports in Murung Raya Regency from a Development Perspective - Indra Jaya Saputra; Laila Refiana Said; Eprinalia A; Patardo Haholongan Nainggolan (Westscience Press, 2026)
This study aims to analyze the influence of modern sports penetration on the existence of local recreational sports in Murung Raya Regency from a development perspective. The background of this study is based on the tendency of marginalization of traditional sports due to the dominance of modern sports driven by policy, media, and infrastructure development. This phenomenon not only impacts changes in recreation patterns, but also has implications for weakening social capital and community cohesion. The method used is a qualitative-explanatory approach with a case study design and a development ethnography approach. Data were collected through in-depth interviews, participant observation, Focus Group Discussions (FGDs), and analysis of regional policy documents. The analysis was conducted using McDonaldization theory, social capital theory, and a post-developmentalist perspective. The results show that the dominance of modern sports occurs through three main mechanisms: institutional (policy and budget), cultural (perception of modernity), and spatial (conversion of public space). This shift has resulted in decreased community participation in traditional sports, weakened cross-generational social interaction, and reduced collective capacity in participatory development. The conclusion of this study confirms that the marginalization of local recreational sports is a structural problem that has implications for the socio-cultural resilience of the community. Therefore, a community-based policy model is needed that integrates traditional sports into regional development as an instrument for strengthening social cohesion and local identity.